Polylactic acid composite fiber membrane as well as preparation method and application thereof
Through electrospinning, annealing and microwave-assisted hydrothermal synthesis technology, polylactic acid composite fiber membranes with high filtration performance, heat resistance and mechanical properties were prepared, solving the problems of low filtration efficiency and poor heat resistance of polylactic fiber membranes in the field of air filtration.
Patent Information
- Application Number
- CN202411628835.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-14
- Publication Date
- 2025-02-25
AI Technical Summary
The low filtration efficiency and poor heat resistance of polylactic fiber membranes in the field of air filtration limit their use in high-efficiency air filtration applications.
Two-component polylactic fiber membranes were prepared by electrospinning technology, and a tautically composite structure was formed by annealing. Then, ZIF-8 crystals were grown in situ on the surface of the fiber membrane using microwave-assisted hydrothermal synthesis to improve the specific surface area and adsorption capacity of the fiber membrane.
The filtration performance, heat resistance and mechanical properties of the polylactic acid composite fiber membrane are significantly improved, and can efficiently filter tiny particles in the air and maintain stable performance under high temperature environments.
Smart Images

Figure CN119507212A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of polylactic acid fiber membranes, and in particular to a polylactic acid composite fiber membrane and a preparation method and application thereof. Background Art
[0002] Polylactic acid (PLA) fiber membranes are widely used in many fields due to their biodegradability, good mechanical properties and environmental friendliness. In the textile industry, PLA fibers are used to make clothing and textiles, providing a sustainable alternative and reducing dependence on petroleum-based synthetic fibers. In the field of packaging materials, PLA is used in food and beverage packaging due to its transparency and barrier properties, reducing plastic pollution. In the medical field, PLA fibers are used as surgical sutures, drug release carriers, and tissue engineering scaffolds due to their biocompatibility and absorbability. However, in the field of air filtration, although PLA fiber membranes have shown great application potential, their filtration effect has not reached the ideal state, which is mainly due to the inherent physical and chemical property limitations of PLA fiber membranes.
[0003] The filtration problems of polylactic acid fiber membranes are mainly reflected in two aspects: First, the filtration efficiency is not high. The porosity and specific surface area of PLA fiber membranes are relatively low, resulting in limited capture capacity of tiny particles, such as PM2.5, especially in situations where high-efficiency filtration is required, and its filtration effect is often unsatisfactory. Second, the poor heat resistance affects its use in high-temperature environments. The low melting point of PLA (about 155-160°C) means that the fiber membrane is easily deformed or melted at high temperatures, which limits its use in certain industrial applications, such as high-temperature exhaust gas filtration. In addition, the surface charge of PLA fiber membranes is low, which is not conducive to enhancing the capture of particles through electrostatic effects, which is also an important factor affecting its filtration efficiency. Therefore, although PLA fiber membranes have shown advantages in many fields, in air filtration applications, the lack of its filtration effect has become a key issue restricting its wider use. Summary of the invention
[0004] The main purpose of the present invention is to provide a polylactic acid composite fiber membrane and a preparation method and application thereof, so as to solve the problems of low air filtration efficiency and poor heat resistance of the polylactic acid fiber membrane in the prior art.
[0005] In order to achieve the above object, according to a first aspect of the present invention, a method for preparing a polylactic acid composite fiber membrane is provided, comprising the following steps:
[0006] S1, dissolving PLLA and PDLA in a first solvent to obtain a PLLA solution and a PDLA solution respectively;
[0007] S2, using PLLA solution and PDLA solution for electrospinning to obtain a bicomponent polylactic acid fiber membrane;
[0008] S3, annealing the two-component polylactic acid fiber membrane to obtain a stereocomposite polylactic acid fiber membrane;
[0009] S4, dissolving the zinc salt and the organic ligand in a second solvent to obtain a mixed solution; mixing the mixed solution and the stereocomplex polylactic acid fiber membrane to obtain a mixture;
[0010] S5, subjecting the mixture to microwave-assisted hydrothermal synthesis, washing, and drying to obtain a polylactic acid composite fiber membrane.
[0011] Furthermore, in S1, the first solvent is at least one of chloroform, acetone, ethyl acetate, dimethylformamide, ethanol, dichloromethane, and chloroform.
[0012] Furthermore, in S1, the weight average molecular weight of PLLA is 100,000 to 400,000.
[0013] Furthermore, in S1, the weight average molecular weight of PDLA is 50,000 to 300,000.
[0014] Furthermore, in S1, the mass fraction of PLLA in the PLLA solution is 0.5% to 15%, and the mass fraction of PDLA in the PDLA solution is 0.5% to 15%.
[0015] Furthermore, in S2, the volume ratio of the PLLA solution and the PDLA solution consumed by electrospinning is (1:1) to (3:2).
[0016] Furthermore, in S2, the electrospinning method is at least one of coaxial electrospinning, parallel electrospinning, double-needle electrospinning, and single-needle electrospinning.
[0017] Further preferably, in S2, the electrospinning method is coaxial electrospinning.
[0018] Furthermore, in S2, the conditions for electrospinning are: voltage 10-30 kV, temperature 20-60°C, humidity 20%-60%, spinning solution consumption rate 0.1-10 mL / h, receiving distance 10-32 cm, and inner diameter of the spinning needle 0.5-1.37 mm.
[0019] Furthermore, in S2, the average diameter of the fibers in the bicomponent polylactic acid fiber membrane is 200 to 1300 nm.
[0020] Furthermore, in S3, the annealing temperature is 30 to 150° C., and the time is 1 to 5 hours.
[0021] Furthermore, in S4, the second solvent is at least one of dichloromethane, chloroform, dimethylformamide, ethanol, methanol, and deionized water.
[0022] Furthermore, in S4, the zinc salt is at least one of zinc nitrate, zinc chloride, zinc sulfate and zinc acetate.
[0023] Furthermore, in S4, the organic ligand is 2-methylimidazole.
[0024] Furthermore, in S4, the concentration of zinc salt in the zinc salt solution is 0.01 to 2 mol / L, and the molar ratio of the organic ligand to the zinc salt is 5:1 to 10:1.
[0025] Furthermore, in S5, the conditions for microwave-assisted hydrothermal synthesis are: microwave reactor output power 200-5000 W, reaction temperature 60-100° C., reaction time 10-80 minutes.
[0026] Furthermore, in S5, the drying temperature is 60 to 100° C. and the drying time is 12 to 24 hours.
[0027] According to a second aspect of the present invention, there is provided a polylactic acid composite fiber membrane prepared by the preparation method according to the first aspect of the present invention.
[0028] Furthermore, the polylactic acid composite fiber membrane contains ZIF-8 crystals, and the mass fraction of the ZIF-8 crystals is 1% to 5%.
[0029] According to a third aspect of the present invention, there is provided an application of the polylactic acid composite fiber membrane according to the second aspect of the present invention in the field of air filtration.
[0030] By applying the technical solution of the present invention, a stereocomposite polylactic acid fiber membrane is obtained by annealing, which has high structural stability, excellent heat resistance and mechanical properties, and can broaden its application in the field of air filtration. In addition, MOF crystals are grown in situ on the surface of polylactic acid fibers by microwave-assisted hydrothermal synthesis, which has strong structural stability and high loading of MOF crystals, and can effectively increase the specific surface area of the polylactic acid composite fiber membrane and improve adsorption and filtration capabilities. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 This is a scanning electron microscope image of the polylactic acid composite fiber membrane in Example 1.
[0032] Figure 2 This is a scanning electron microscope image of the polylactic acid composite fiber membrane in Comparative Example 1. DETAILED DESCRIPTION
[0033] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.
[0034] As described in the background of the present invention, the prior art has the problem that the air filtration effect of the polylactic acid fiber membrane is poor and the heat resistance is poor. In order to solve the above technical problems, in a typical embodiment of the present invention, a method for preparing a polylactic acid composite fiber membrane is provided, comprising the following steps:
[0035] S1, dissolving PLLA and PDLA in a first solvent to obtain a PLLA solution and a PDLA solution respectively;
[0036] S2, using PLLA solution and PDLA solution for electrospinning to obtain a bicomponent polylactic acid fiber membrane;
[0037] S3, annealing the two-component polylactic acid fiber membrane to obtain a stereocomposite polylactic acid fiber membrane;
[0038] S4, dissolving the zinc salt and the organic ligand in a second solvent to obtain a mixed solution; mixing the mixed solution and the stereocomplex polylactic acid fiber membrane to obtain a mixture;
[0039] S5, subjecting the mixture to microwave-assisted hydrothermal synthesis, washing, and drying to obtain a polylactic acid composite fiber membrane.
[0040] In the present invention, firstly, a two-component polylactic acid fiber membrane is prepared by electrostatic spinning technology. This method can prepare a fiber membrane with high porosity and large specific surface area, and provides an ideal substrate for the in-situ growth of subsequent MOF crystals such as ZIF-8 crystals. It can obtain a two-component polylactic acid fiber membrane with uniform diameter and regular morphology by controlling the spinning conditions, thereby improving the mechanical strength and filtering performance of the fiber membrane. The crystal transformation of the polylactic acid fiber membrane can be controlled by annealing treatment to form a more stable three-dimensional composite structure, thereby significantly improving the thermal stability and mechanical strength of the polylactic acid fiber membrane, and also helps to maintain the uniform distribution of the subsequently generated MOF crystals on the fiber surface, and prevents the MOF crystals from falling off or uneven distribution due to fiber deformation. Microwave-assisted hydrothermal synthesis is a fast and efficient crystal growth technology. Compared with the traditional hydrothermal synthesis method, microwaves can provide uniform and rapid heating in the reaction system, significantly shortening the growth time of MOF crystals, while improving the uniformity and stability of crystal growth; in addition, microwave-assisted technology not only accelerates the formation of MOF crystals such as ZIF-8, but also promotes the close combination of crystals and the fiber membrane surface, thereby effectively improving the loading amount and distribution uniformity of MOF, thereby enhancing the adsorption capacity and filtration efficiency of polylactic acid composite fiber membrane. The combination of the above three technologies can comprehensively improve the filtration performance, heat resistance, mechanical properties and stability of polylactic acid fiber membrane. Electrospinning technology provides a fiber membrane substrate with a high specific surface area, microwave-assisted hydrothermal synthesis promotes the rapid and uniform growth of MOF crystals, and annealing stereocomplexation technology enhances the thermal stability and structural strength of the fiber membrane. The combination of the three makes the polylactic acid composite fiber membrane show excellent filtration performance and durability while maintaining biodegradability and environmental friendliness, meeting the needs of high-efficiency air filtration materials.
[0041] In some embodiments, in S1, the first solvent is at least one of chloroform, acetone, ethyl acetate, dimethylformamide, ethanol, dichloromethane, and chloroform.
[0042] The above solvents show good solubility for polylactic acid and can dissolve polylactic acid quickly and fully to form a uniform and stable spinning solution, which is beneficial for preparing a polylactic acid fiber membrane with good continuity and narrow diameter distribution.
[0043] In some embodiments, in S1, the weight average molecular weight of PLLA is 100,000 to 400,000, and the weight average molecular weight of PDLA is 50,000 to 300,000.
[0044] The weight-average molecular weight of PLLA and PDLA directly affects the rheological properties of the spinning solution, and thus affects the electrospinning process and the quality of the fiber membrane. High molecular weight PLLA (100,000-400,000) and PDLA (50,000-300,000) provide sufficient intermolecular interaction forces, making the spinning solution have suitable viscosity and elasticity, which is conducive to the formation of fine and uniform nanofibers during the electrospinning process, thereby obtaining a polylactic acid fiber membrane with optimized porosity and specific surface area.
[0045] In some embodiments, in S1, the mass fraction of PLLA in the PLLA solution is 0.5% to 15%, and the mass fraction of PDLA in the PDLA solution is 0.5% to 15%.
[0046] The electrospinning process has strict requirements on the viscosity and surface tension of the spinning solution to form continuous and uniform nanofibers. Within the above mass fraction range, PLLA and PDLA solutions can achieve suitable rheological properties, which not only ensures the fluidity of the solution, but also provides sufficient viscosity to support the formation of fibers during the electrospinning process; in addition, the spinning solution will affect the diameter and pore structure of the fiber, which will in turn affect the loading rate of the MOF crystal. By making the above restrictions, MOF crystals can grow more effectively on the fiber surface, increase the loading amount and uniformity, and thus enhance the adsorption and filtration performance of the filter membrane. In addition, the appropriate mass fraction helps to promote the arrangement and orientation between the PLLA and PDLA molecular chains during the annealing process, forming a more stable stereocomposite structure.
[0047] In some embodiments, in S2, the volume ratio of the PLLA solution and the PDLA solution consumed by electrospinning is (1:1) to (3:2).
[0048] The ratio of PLLA and PDLA in the solution is directly related to the stereocomposite structure of the fiber membrane formed during the electrospinning process. By precisely controlling the consumption volume ratio of the two solutions, the ratio of PLLA to PDLA in the fiber membrane can be adjusted, thereby optimizing the stereocomposite degree inside the fiber, and finally obtaining a polylactic acid fiber membrane with higher heat resistance and better mechanical properties.
[0049] In some embodiments, in S2, the electrospinning method is at least one of coaxial electrospinning, parallel electrospinning, double-needle electrospinning, and single-needle electrospinning; coaxial electrospinning is further preferred. The polylactic acid fiber membrane prepared by coaxial electrospinning has higher mechanical strength and is easier to generate a stereocomposite polylactic acid fiber membrane, thereby enhancing the interception effect on particulate matter in the air.
[0050] In some embodiments, in S2, the conditions for electrospinning are: voltage 10-30 kV, temperature 20-60°C, humidity 20%-60%, spinning solution consumption rate 0.1-10 mL / h, receiving distance 10-32 cm, and inner diameter of the spinning needle 0.5-1.37 mm.
[0051] The diameter of the fibers in the two-component polylactic acid fiber membrane prepared under the above conditions is 200-1300 nm, and the pore structure of the two-component polylactic acid fiber membrane is better, which is beneficial to improving the filtration performance of the polylactic acid composite fiber membrane.
[0052] In some embodiments, in S3, the annealing temperature is 30 to 150° C., and the time is 1 to 5 hours.
[0053] Annealing is carried out under the above conditions, and the structure of the obtained stereocomposite polylactic acid fiber membrane is more stable and has better mechanical strength. It is also conducive to the deposition of more MOF crystals and improves the filtration efficiency.
[0054] In some embodiments, in S4, the second solvent is at least one of dichloromethane, chloroform, dimethylformamide, ethanol, methanol, and deionized water.
[0055] The above solvents have good solubility for zinc salts, which is conducive to the formation of uniform MOF crystals on the polylactic acid fiber membrane.
[0056] In some embodiments, in S4, the zinc salt is at least one of zinc nitrate, zinc chloride, zinc sulfate, and zinc acetate, and the organic ligand is 2-methylimidazole. Further, the concentration of the zinc salt in the zinc salt solution is 0.01 to 2 mol / L, and the molar ratio of the organic ligand to the zinc salt is 5:1 to 10:1.
[0057] The above ingredients can easily prepare ZIF-8 crystals with complete crystal structure. ZIF-8 crystals can provide a large number of adsorption sites due to their unique pore structure and high specific surface area, effectively capturing particulate matter in the air, especially fine particles such as PM2.5. Its polar functional groups and high surface potential can also enhance electrostatic adsorption, thereby further improving filtration efficiency.
[0058] In some embodiments, in S5, the conditions for microwave-assisted hydrothermal synthesis are: microwave reactor output power 200-5000 W, reaction temperature 60-100° C., reaction time 10-80 minutes.
[0059] Microwave-assisted hydrothermal synthesis provides fast and uniform energy input through microwave radiation, which can significantly accelerate the growth reaction of ZIF-8 crystals on the surface of polylactic acid fibers and shorten the reaction time. The set reaction power, temperature and time range allow for fine control of the ZIF-8 crystal growth process to ensure that the size, morphology and distribution of the crystals meet expectations. This crystal morphology is conducive to improving the bonding strength between MOF and polylactic acid fibers, enhancing the stability and durability of the fiber membrane, and enhancing the adhesion of the crystals on the fiber surface, improving the mechanical strength of the fiber membrane and the loading efficiency of MOF crystals. In summary, by controlling the conditions of microwave-assisted hydrothermal synthesis within the above range, the growth of ZIF-8 crystals can be accelerated, the quality of the crystals and the bonding strength with the fiber can be improved, and the fine control of the crystal loading can be achieved. At the same time, modification under mild conditions is conducive to improving the comprehensive performance of polylactic acid fiber membranes, including filtration efficiency, dust holding capacity, mechanical strength and heat resistance, providing strong technical support for the development of high-efficiency air filtration materials.
[0060] In some embodiments, in S5, the drying temperature is 60-100° C. and the drying time is 12-24 hours.
[0061] Drying under the above conditions can improve the stability of MOF crystals, and is beneficial to maintaining the good mechanical strength of the polylactic acid composite fiber membrane, and has high drying efficiency.
[0062] In another typical embodiment of the present invention, a polylactic acid composite fiber membrane is provided, and the polylactic acid composite fiber membrane is prepared by the preparation method of the first aspect of the present invention. Further, the polylactic acid composite fiber membrane contains ZIF-8 crystals, and the mass fraction of ZIF-8 crystals is 1% to 5%. Further, in some embodiments, the thickness of the polylactic acid composite fiber membrane is 10 to 200 μm. The above-mentioned polylactic acid composite fiber membrane has good mechanical strength, and its air filtration performance is good, and it can efficiently filter particulate matter in the air under low resistance conditions.
[0063] In another typical embodiment of the present invention, there is provided an application of the polylactic acid composite fiber membrane in the above embodiment of the present invention in the field of air filtration.
[0064] The present application is further described in detail below in conjunction with specific embodiments. These embodiments should not be construed as limiting the scope of protection claimed in the present application.
[0065] Example 1
[0066] An embodiment of the polylactic acid composite fiber membrane of the present invention, the preparation method of the polylactic acid composite fiber membrane in this embodiment is as follows:
[0067] S1, dissolving PLLA (weight average molecular weight of 100,000) and PDLA (weight average molecular weight of 50,000) in chloroform, respectively, to obtain a PLLA solution and a PDLA solution with a mass fraction of 0.5% for PLLA and 0.5% for PDLA;
[0068] S2, using coaxial electrospinning, PLLA solution as the inner spinning solution, PDLA solution as the outer spinning solution, the consumption rate of both was 0.1mL / h, the spinning voltage was 10kV, the temperature was 25℃, the humidity was 40%, the receiving distance was 15cm, the inner diameter of the spinning needle was 0.84mm, and tin foil was used as the receiving substrate to obtain a two-component polylactic acid fiber membrane (fiber diameter was 1236±16.2nm);
[0069] S3, annealing the two-component polylactic acid fiber membrane at 150° C. for 1 h to obtain a stereocomposite polylactic acid fiber membrane;
[0070] S4, dissolving zinc acetate and 2-methylimidazole in methanol to obtain a mixed solution with a zinc acetate concentration of 0.01 mol / L, wherein the molar ratio of 2-methylimidazole to zinc acetate in the mixed solution is 10:1, and then mixing the mixed solution with a stereocomposite polylactic acid fiber membrane to obtain a mixture;
[0071] S5, the mixture was subjected to microwave-assisted hydrothermal synthesis, the microwave reactor output power was 300 W, the reaction temperature was 60°C, the reaction time was 80 min, after the reaction was completed, it was washed three times with deionized water to remove the loosely bound ZIF-8 crystals, and finally dried in an oven at 60°C for 24 h to obtain a polylactic acid composite fiber membrane, wherein the mass fraction of ZIF-8 crystals was 1%, and the thickness of the polylactic acid composite fiber membrane was 46 μm.
[0072] Example 2
[0073] An embodiment of the polylactic acid composite fiber membrane of the present invention, the preparation method of the polylactic acid composite fiber membrane in this embodiment is as follows:
[0074] S1, dissolving PLLA (weight average molecular weight of 150,000) and PDLA (weight average molecular weight of 150,000) in acetone to obtain a PLLA solution and a PDLA solution with a mass fraction of PLLA and PDLA of 15% respectively;
[0075] S2, using parallel electrospinning technology, the consumption rate of PLLA solution and PDLA solution was controlled to be 10mL / h, the spinning voltage was 25kV, the temperature was 30℃, the humidity was 50%, the receiving distance was 26cm, the inner diameter of the spinning needle was 0.61mm, and tin foil was used as the receiving substrate to obtain a two-component polylactic acid fiber membrane (fiber diameter was 568±6.8nm);
[0076] S3, annealing the two-component polylactic acid fiber membrane at 100° C. for 5 hours to obtain a stereocomposite polylactic acid fiber membrane;
[0077] S4, dissolving zinc acetate and 2-methylimidazole in ethanol to obtain a mixed solution with a zinc acetate concentration of 0.01 mol / L, wherein the molar ratio of 2-methylimidazole to zinc acetate in the mixed solution is 5:1, and mixing the mixed solution with a stereocomposite polylactic acid fiber membrane to obtain a mixture;
[0078] S5, the mixture was subjected to microwave-assisted hydrothermal synthesis, the microwave reactor output power was 500 W, the reaction temperature was 100 ° C, the reaction time was 30 minutes, and after the reaction was completed, it was washed three times with deionized water to remove the loosely bound ZIF-8 crystals, and finally dried in an oven at 100 ° C for 12 h to obtain a polylactic acid composite fiber membrane, wherein the mass fraction of ZIF-8 crystals was 5%, and the thickness of the polylactic acid composite fiber membrane was 96 μm.
[0079] Example 3
[0080] An embodiment of the polylactic acid composite fiber membrane of the present invention, the preparation method of the polylactic acid composite fiber membrane in this embodiment is as follows:
[0081] S1, dissolving PLLA (weight average molecular weight of 200,000) and PDLA (weight average molecular weight of 200,000) in dichloromethane to obtain a PLLA solution and a PDLA solution in which the mass fractions of PLLA and PDLA are both 10%;
[0082] S2, using single needle electrospinning technology, PLLA solution and PDLA solution were mixed, the consumption rate of the mixed solution was controlled to be 10mL / h, the spinning voltage was 25kV, the temperature was 25℃, the humidity was 45%, the receiving distance was 32cm, the inner diameter of the spinning needle was 1.37mm, and tin foil was used as the receiving substrate to obtain a two-component polylactic acid fiber membrane (fiber diameter was 489±5.7nm);
[0083] S3, annealing the two-component polylactic acid fiber membrane at 100° C. for 1 h to obtain a stereocomposite polylactic acid fiber membrane;
[0084] S4, dissolving zinc acetate and 2-methylimidazole in methanol to obtain a mixed solution with a zinc acetate concentration of 1 mol / L, wherein the molar ratio of 2-methylimidazole to zinc acetate in the mixed solution is 8:1, and mixing the mixed solution with a stereocomposite polylactic acid fiber membrane to obtain a mixture;
[0085] S5, the mixture was subjected to microwave-assisted hydrothermal synthesis, the microwave reactor output power was 400 W, the reaction temperature was 90 ° C, the reaction time was 50 min, after the reaction was completed, it was washed three times with deionized water to remove the loosely bound ZIF-8 crystals, and finally dried in an oven at 100 ° C for 12 h to obtain a polylactic acid composite fiber membrane, wherein the mass fraction of ZIF-8 crystals was 4%, and the thickness of the polylactic acid composite fiber membrane was 77 μm.
[0086] Example 4
[0087] An embodiment of the polylactic acid composite fiber membrane of the present invention, the preparation method of the polylactic acid composite fiber membrane in this embodiment is as follows:
[0088] S1, dissolving PLLA (weight average molecular weight of 100,000) and PDLA (weight average molecular weight of 300,000) in dimethylformamide, respectively, to obtain a PLLA solution and a PDLA solution with a mass fraction of 12% for PLLA and PDLA;
[0089] S2, using coaxial electrospinning, PLLA solution as the inner spinning solution, PDLA solution as the outer spinning solution, the consumption rate of both was 10mL / h, the spinning voltage was 25kV, the temperature was 22℃, the humidity was 50%, the receiving distance was 15cm, the inner diameter of the spinning needle was 0.51mm, and tin foil was used as the receiving substrate to obtain a two-component polylactic acid fiber membrane (fiber diameter was 523±6.8nm);
[0090] S3, annealing the two-component polylactic acid fiber membrane at 100° C. for 0.2 h to obtain a stereocomposite polylactic acid fiber membrane;
[0091] S4, dissolving zinc acetate and 2-methylimidazole in deionized water to obtain a mixed solution with a zinc acetate concentration of 0.02 mol / L, wherein the molar ratio of 2-methylimidazole to zinc acetate in the mixed solution is 6:1, and mixing the mixed solution with a stereocomposite polylactic acid fiber membrane to obtain a mixture;
[0092] S5, the mixture was subjected to microwave-assisted hydrothermal synthesis, the microwave reactor output power was 550 W, the reaction temperature was 80 ° C, the reaction time was 30 minutes, and after the reaction was completed, it was washed three times with deionized water to remove the loosely bound ZIF-8 crystals, and finally dried in an oven at 100 ° C for 12 h to obtain a polylactic acid composite fiber membrane, wherein the mass fraction of ZIF-8 crystals was 3%, and the thickness of the polylactic acid composite fiber membrane was 84 μm.
[0093] Example 5
[0094] An embodiment of the polylactic acid composite fiber membrane of the present invention, the preparation method of the polylactic acid composite fiber membrane in this embodiment is as follows:
[0095] S1, dissolving PLLA (weight average molecular weight of 100,000) and PDLA (weight average molecular weight of 50,000) in chloroform, respectively, to obtain a PLLA solution and a PDLA solution with a mass fraction of 0.5% for PLLA and 0.5% for PDLA;
[0096] S2, using parallel electrospinning technology, the consumption rate of PLLA solution and PDLA solution was 0.1mL / h, the spinning voltage was 10kV, the temperature was 25℃, the humidity was 40%, the receiving distance was 15cm, the inner diameter of the spinning needle was 0.84mm, and a two-component polylactic acid fiber membrane (fiber diameter was 1164.8±24.3nm) was obtained;
[0097] S3, annealing the two-component polylactic acid fiber membrane at 150° C. for 1 h to obtain a stereocomposite polylactic acid fiber membrane;
[0098] S4, dissolving zinc acetate and 2-methylimidazole in methanol to obtain a mixed solution with a zinc acetate concentration of 0.01 mol / L, wherein the molar ratio of 2-methylimidazole to zinc acetate in the mixed solution is 10:1, and mixing the mixed solution with a stereocomposite polylactic acid fiber membrane to obtain a mixture;
[0099] S5, the mixture was subjected to microwave-assisted hydrothermal synthesis, the microwave reactor output power was 300 W, the reaction temperature was 60°C, the reaction time was 80 min, after the reaction was completed, it was washed three times with deionized water to remove the loosely bound ZIF-8 crystals, and finally dried in an oven at 60°C for 24 h to obtain a polylactic acid composite fiber membrane, wherein the mass fraction of ZIF-8 crystals was 1%, and the thickness of the polylactic acid composite fiber membrane was 39 μm.
[0100] Example 6
[0101] An embodiment of the polylactic acid composite fiber membrane of the present invention, the preparation method of the polylactic acid composite fiber membrane in this embodiment is as follows:
[0102] S1, dissolving PLLA (weight average molecular weight of 100,000) and PDLA (weight average molecular weight of 50,000) in chloroform, respectively, to obtain a PLLA solution and a PDLA solution with a mass fraction of 0.5% for PLLA and 0.5% for PDLA;
[0103] S2, using single needle electrospinning technology, PLLA solution and PDLA solution were mixed, the consumption rate of the mixed solution was 0.1mL / h, the spinning voltage was 10kV, the temperature was 25℃, the humidity was 40%, the receiving distance was 15cm, the inner diameter of the spinning needle was 0.84mm, and tin foil was used as the receiving substrate to obtain a two-component polylactic acid fiber membrane (fiber diameter was 1674±27.8nm);
[0104] S3, annealing the two-component polylactic acid fiber membrane at 150° C. for 1 h to obtain a stereocomposite polylactic acid fiber membrane;
[0105] S4, dissolving zinc acetate and 2-methylimidazole in methanol to obtain a mixed solution with a zinc acetate concentration of 0.01 mol / L, wherein the molar ratio of 2-methylimidazole to zinc acetate in the mixed solution is 10:1, and mixing the mixed solution with a stereocomposite polylactic acid fiber membrane to obtain a mixture;
[0106] S5, the mixture was subjected to microwave-assisted hydrothermal synthesis, the microwave reactor output power was 300 W, the reaction temperature was 60°C, the reaction time was 80 min, after the reaction was completed, it was washed three times with deionized water to remove the loosely bound ZIF-8 crystals, and finally dried in an oven at 60°C for 24 h to obtain a polylactic acid composite fiber membrane, wherein the mass fraction of ZIF-8 crystals was 1%, and the thickness of the polylactic acid composite fiber membrane was 42 μm.
[0107] Comparative Example 1
[0108] A polylactic acid composite fiber membrane, the preparation method of which is different from that of Example 1 only in that microwave-assisted hydrothermal synthesis technology is not used in S5, specifically:
[0109] 2-Methylimidazole and zinc acetate were dissolved in deionized water to obtain a mixed solution, wherein the concentration of zinc acetate in the mixed solution was 0.01 mol / L, and the molar ratio of 2-methylimidazole to zinc acetate was 10:1. A 0.01 mol / L hexadecyltrimethylammonium bromide solution was continuously added dropwise to the mixed solution, with a total of 5 mL being added dropwise. The stereocomposite polylactic acid fiber membrane was immersed in the mixed solution at 60°C for 30 min. After the reaction was completed, the stereocomposite polylactic acid fiber membrane was washed three times with deionized water to remove loosely bound ZIF-8 crystals. Finally, the membrane was dried in an oven at 60°C for 24 h to obtain a polylactic acid composite fiber membrane, wherein the mass fraction of the ZIF-8 crystals was 1%, and the thickness of the polylactic acid composite fiber membrane was 12 μm.
[0110] Comparative Example 2
[0111] A polylactic acid composite fiber membrane, the preparation method of which is different from that of Example 2 only in that the parallel electrospinning technology is replaced by the single needle electrospinning technology, as follows:
[0112] Single-needle electrospinning was performed with a PLLA solution with a PLLA mass fraction of 150,000, a PLLA solution consumption rate of 10 mL / h, a spinning voltage of 25 kV, a temperature of 30 ° C, a humidity of 50%, a receiving distance of 26 cm, an inner diameter of the spinning needle of 1.37 mm, and tin foil as a receiving substrate to obtain a polylactic acid fiber membrane (fiber diameter of 643 ± 11.2 nm);
[0113] Dissolving zinc acetate and 2-methylimidazole in deionized water to obtain a mixed solution with a zinc acetate concentration of 2 mol / L, wherein the molar ratio of 2-methylimidazole to zinc acetate in the mixed solution is 5:1, and placing a polylactic acid fiber membrane in the mixed solution to obtain a mixture;
[0114] The mixture was subjected to microwave-assisted hydrothermal synthesis, with an output power of 500 W in the microwave reactor, a reaction temperature of 100°C, and a reaction time of 30 min. After the reaction, it was washed three times with deionized water to remove loosely bound ZIF-8 crystals, and finally dried in an oven at 100°C for 12 h to obtain a polylactic acid composite fiber membrane, in which the mass fraction of ZIF-8 crystals was 5% and the thickness of the polylactic acid composite fiber membrane was 89 μm.
[0115] Performance Testing
[0116] 1) Morphology: The surface morphology of the polylactic acid composite fiber membrane was observed by field emission scanning electron microscopy (model JSM-7900F, JEOL);
[0117] 2) Specific surface area: The nitrogen adsorption isotherm was measured at 77 K using a gas adsorption instrument (ASAP 2060, Micromeritics, USA);
[0118] 3) Tensile properties: The obtained fiber membrane was cut to obtain tensile specimens, and the tensile properties of the composite material were tested using a universal tensile machine (model 4403, sensor 100N) from Instron, USA, according to the plastic tensile properties test standard ASTMD638-2003 of the American Society for Testing and Materials. Three parallel test samples were taken for each group, and the average value of the results was taken;
[0119] 4) Thermal properties: The thermal properties of the obtained fiber membrane were analyzed using a DSC-6200 differential scanning calorimeter (DSC) from Perkin Elmer, USA. 3-5 mg of sample powder was placed in a crucible and pressed tightly. Nitrogen protection was used during the test, with a gas flow rate of 50 mL / min, a heating rate of 20°C / min, and a heating range of 30-250°C.
[0120] 5) Surface potential: A non-contact electrostatic meter (VM54XQS, Quatek, USA) was used to test the surface potential of the nanofiber membrane. The test height was 2 cm, the temperature and humidity were constant at 25°C and 45%, and 20 data points were randomly collected for each sample and the average value was taken.
[0121] 6) Filtration performance: The fiber membrane (area 113.04cm 2) air filtration performance, the gas flow rate was set to 85L / min, and the particle size range of NaCl atomized particles produced by the aerosol generator was 0.1-10μm. Each group of fiber membranes was tested at 3 different positions, and the results were averaged;
[0122] 7) Dust holding capacity performance: Under the above filtration conditions, after continuous filtration for 24 hours, the fiber membrane is taken out and weighed, and the dust holding capacity (DHC) of the filter material is calculated as follows. DHC = (M1-M0) / A; where M1 is the mass of the fiber membrane after the dust holding test, g; M0 is the mass of the unfiltered fiber membrane, g; A is the effective filtration area, 113.04 cm 2 .
[0123] The test results are shown in Tables 1 and 2.
[0124] Table 1
[0125]
[0126]
[0127] Table 2
[0128]
[0129] Table 1 compares the specific surface area, mechanical properties and filtration performance test results of the polylactic acid composite fiber membranes obtained in the examples and comparative examples. Examples 1 to 6 have higher specific surface areas (102.2 m 2 / g~236.4m 2 / g), which greatly increases the roughness of the fiber surface and effectively improves the filtration performance. A higher specific surface area usually indicates that the material has more interception sites and more attachment sites for particles on the fiber surface, which has a stronger interception effect on particles and helps to improve filtration efficiency and dust holding capacity.
[0130] In addition, Examples 1 to 6 all have high breaking strength (12.5 MPa to 18.3 MPa), reflecting excellent mechanical properties, and fully meeting the mechanical property requirements of polylactic acid fiber membranes in the field of filtration materials. In addition, by comparing the performance test results of Examples 1 and 5 to 6, it can be found that the mechanical properties of the polylactic acid composite fiber membrane prepared by the coaxial electrospinning method are better. The breaking strengths of Comparative Examples 1 and 2 are only 10.3 MPa and 9.8 MPa, which are mainly caused by uneven loading of ZIF-8 crystals and softening of fibers.
[0131] It is also of great significance that Examples 1 to 6 all exhibit extremely high surface potentials (7.7 kV to 11.2 kV), among which the surface potentials of Examples 1 to 4 hardly decay over time, proving to have extremely high long-term stability. In particular, the initial value of the surface potential of Example 1 is as high as 11.2 kV, which is 22 times that of Comparative Example 1 and nearly 5 times that of Comparative Example 2; and after 30 days, the surface potential of Example 1 is still maintained at 11.0 kV. The filtration efficiency of Examples 1 to 6 is relatively high, all above 90%, especially in PM 0.3 Excellent performance in particle filtration efficiency.
[0132] As shown in Table 2, Examples 1 to 6 have good heat resistance, and the improvement of heat resistance promotes the degree of in-situ MOFization. Examples 1 to 6 all show a high dust holding capacity, especially Example 2, which is almost 3 times that of the comparative example.
[0133] like Figure 1 As shown, in the polylactic acid composite fiber membrane in Example 1, MOF crystals are evenly distributed and attached to the fiber surface to form a continuous covering layer. The bonding interface between the MOF crystals and the fiber matrix is clear without obvious peeling or falling off, indicating that there is good interface bonding between MOF and the fiber matrix. Figure 2 This is a scanning electron microscope image of the polylactic acid composite fiber membrane in Comparative Example 1. It can be seen from the figure that the size uniformity of the MOF crystals is relatively poor, and stress concentration points may be generated during the stretching process, which leads to reduced mechanical properties of the polylactic acid composite fiber membrane. At the same time, the uneven distribution of interception sites formed on the fiber surface will also lead to low particle filtration efficiency.
[0134] This shows that the technical solution proposed in this patent makes the ZIF-8 crystal have good surface properties and structural regularity, the loading degree of ZIF-8 in the polylactic acid fiber membrane is significantly improved, and the polylactic acid composite fiber membrane obtains high surface potential and high filtration performance. These are likely due to: (1) The microwave-assisted method not only greatly shortens the reaction time, but also obtains ZIF-8 crystals with better structural regularity; (2) The use of stereocomposite polylactic acid fiber membrane with a higher softening temperature as the in-situ growth site broadens the conditions for the in-situ growth of ZIF-8, which is beneficial to improving MOF activity and increasing binding sites and adhesion strength; (3) By loading ZIF-8 on the fiber surface, it is beneficial to maintain the high surface potential of the fiber membrane, achieve the stable and long-term filtration effect of the polylactic acid composite fiber membrane, and expand the application prospects of the polylactic acid fiber membrane.
[0135] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for preparing a polylactic acid composite fiber membrane, characterized in that: The steps include: S1, dissolving PLLA and PDLA in a first / second solvent, respectively, to obtain a PLLA solution and a PDLA solution; S2, using the PLLA solution and the PDLA solution to perform electrospinning to obtain a bi-component polylactic acid fiber membrane; S3, annealing the two-component polylactic acid fiber membrane to obtain a stereocomposite polylactic acid fiber membrane; S4, dissolving the zinc salt and the organic ligand in a second solvent to obtain a mixed solution; mixing the mixed solution and the stereocomplex polylactic acid fiber membrane to obtain a mixture; S5, subjecting the mixture to microwave-assisted hydrothermal synthesis, washing, and drying to obtain the polylactic acid composite fiber membrane.
2. The preparation method according to claim 1, characterized in that: The S1 includes at least one of the following features: (1) The first solvent is at least one of chloroform, acetone, ethyl acetate, dimethylformamide, ethanol, dichloromethane, and chloroform; (2) The weight average molecular weight of the PLLA is 100,000 to 400,000; (3) The weight average molecular weight of the PDLA is 50,000 to 300,000; (4) The mass fraction of PLLA in the PLLA solution is 0.5% to 15%; (5) The mass fraction of the PDLA in the PDLA solution is 0.5% to 15%.
3. The preparation method according to claim 1, characterized in that: The S2 includes at least one of the following features: (1) The volume ratio of the PLLA solution and the PDLA solution consumed by the electrospinning is (1:1) to (3:2); (2) The electrospinning method is at least one of coaxial electrospinning, parallel electrospinning, double-needle electrospinning, and single-needle electrospinning; (3) The electrospinning conditions are: voltage 10-30 kV, temperature 20-60° C., humidity 20%-60%, spinning solution consumption rate 0.1-10 mL / h, receiving distance 10-32 cm, and spinning needle inner diameter 0.5-1.37 mm; (4) The average diameter of the fibers in the bicomponent polylactic acid fiber membrane is 200 to 1300 nm.
4. The preparation method according to claim 1, characterized in that: In S3, the annealing temperature is 30 to 150° C. and the time is 1 to 5 hours.
5. The preparation method according to claim 1, characterized in that: The S4 includes at least one of the following features: (1) The second solvent is at least one of dichloromethane, chloroform, dimethylformamide, ethanol, methanol, and deionized water; (2) The zinc salt is at least one of zinc nitrate, zinc chloride, zinc sulfate and zinc acetate; (3) The organic ligand is 2-methylimidazole; (4) The concentration of the zinc salt in the zinc salt solution is 0.01 to 2 mol / L, and the molar ratio of the organic ligand to the zinc salt is 5:1 to 10:
1.
6. The preparation method according to any one of claims 1 to 5, characterized in that The conditions of the microwave-assisted hydrothermal synthesis are: the microwave reactor output power is 200-5000W, the reaction temperature is 60-100°C, and the reaction time is 10-80 minutes.
7. The preparation method according to claim 6, characterized in that: The drying temperature is 60-100° C. and the drying time is 12-24 hours.
8. A polylactic acid composite fiber membrane, characterized in that: Prepared by the preparation method according to any one of claims 1 to 7.
9. The polylactic acid composite fiber membrane according to claim 8, characterized in that: The polylactic acid composite fiber membrane contains ZIF-8 crystals, and the mass fraction of the ZIF-8 crystals is 1% to 5%.
10. An application of a polylactic acid composite fiber membrane in the field of air filtration, characterized in that: The polylactic acid composite fiber membrane is prepared by the preparation method described in any one of claims 1 to 7 or is the polylactic acid composite fiber membrane described in claim 8 or 9.